Social media design for dummies - Warner, Janine, 1967- (For dummie, 2014)
Take your social media site to the next level with a top-notch design! By using custom templates, you can create profiles for Facebook and YouTube; design a Twitter background or create a Google+ design; and even bring all your social media together on RebelMouse